How can I show that $\sum _{n=0}^{p-1} (-1)^n \binom{p}{n+1}=1$ where $p$ is a positive integer?

Is this the rule for this proof?

I could not figure it out even using this.

Probably this may be a well-known result, however I could not find.


By the binomial theorem, $$ 0=(1-1)^p=\sum_{j=0}^p(-1)^j{p\choose j}$$ Note that the $j=0$ term in the sum is $1$. Therefore $$ 1=-\sum_{j=1}^p(-1)^j{p\choose j}=\sum_{j=1}^p(-1)^{j-1}{p\choose j}$$ and setting $n=j-1$, this becomes $$ 1=\sum_{n=0}^{p-1}(-1)^n{p\choose n+1}$$

  • $\begingroup$ It needs a simple but smart trick, thanks @carmichael561. $\endgroup$ – Frey Jul 5 '17 at 2:04

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.